Cultural Diplomacy of Pura Mangkunegaran Through the Langenpraja International Roadshow 2022 - Gloria Britania Rambi; Triesanto Romulo Simanjuntak; Petsy Jessy Ismoyo (Badan Penerbit STIEPARI Press, 2025)
Pura Mangkunegaran is a royal palace that serves as a center for the preservation and development of Javanese arts and culture. In an increasingly globalized world, Pura Mangkunegaran has assumed a significant role as a diplomatic window in international relations. After several decades, Pura Mangkunegaran has revived its spirit in carrying out its cultural mission in 2022. This cultural mission was held in three countries: Malaysia, Australia, and Thailand. This study aims to examine the role of Pura Mangkunegaran as a cultural diplomacy actor through the Kemantren Langenpraja International Roadshow 2022. This study employs a qualitative method, collecting data through a literature review and interviews. The results of the study indicate that the cultural diplomacy activities conducted by Pura Mangkunegaran, using art as a tool for cultural diplomacy, have successfully created a positive image in the eyes of the world, receiving appreciation and positive responses from various parties, particularly the international community in the target countries. Additionally, the success of the diplomacy carried out by Pura Mangkunegaran is closely tied to the collaboration between diplomatic actors who served as supporting actors in these activities.